Attitude of Health Care Professionals Towards Voluntary Counseling and Testing for HIV/AIDS - Adesina Omololu Ayodele Adekanbi; Kelvin Ifeanyi Egbuchulem; Omokhoa Adedayo Adeleye; Eronmwon Evbuomwan; Osadolor Abraham King-Inneh (Shahid Sadoughi University of Medical Sciences, 2016)
Introduction: HIV counseling and testing is the vital and preliminary interventional step aimed at reducing the spread of HIV infection. The study was designed to determine the attitude of health care professionals towards voluntary counseling and testing (VCT) for HIV/AIDS at Irrua Specialist Teaching Hospital. Materials & Methods: In this descriptive cross sectional prospective study a self –administered structured questionnaire was used, it contained sections on bio social variables and section aimed at fulfilling the objectives of the study; the participants were medical doctors, nurses, medical laboratory scientists, radiographers, social workers and pharmacists. Data were collated, inputted into a computer and statistical analysis performed using SPSS version 22 software. Descriptive variables were summarized using percentages and proportions for categorical variables. Bivariate analysis was done to test for association between categorical variables using the chi square test; p value of < 0.05 was considered statistically significant. Multiple logistic regressions were performed to identify predictive variables appropriate for the association between socio-demographic and willingness to go for screening. Results: Two hundred and thirty eight questionnaires were administered and statistically analyzed; the group consists of workers mostly females, (55%) aged 21-30 years, (47.8%), married, (52.5%) Christians, (96.2%) medical doctors, (49.2%) of Esan extraction; marital status and occupation of the participants significantly influenced their attitude towards voluntary counseling and testing for HIV/AID. A good percentage of the respondents have the right attitude towards VCT of HIV/AIDS. Conclusion: This study has shown that a good percentage of the respondents have the right attitude towards VCT of HIV/AIDS while a lesser proportion had negative attitude.